Transition of psychological state from recording to live performance : a longitudinal explanatory sequential study in music students from Universiti Malaya during COVID-19 - W. F., Beh; Y. S., Wong; Connie Lim, Keh Nie; J .P. S., Yeoh; K. S. L, Cheah (Moscow State University of Psychology and Education, 2025)
Music students often struggle with music performance anxiety (MPA), which is debilitating stress brought on by performances. However, MPA varies according to the type of performance. Therefore, this study aims to compare the MPA levels of performance recorded versus live. This study also looks at the factors that influence students’ anxiety levels and their views on the various assessment formats. A total of 28 second-year music undergraduates were recruited. Survey questionnaires (K-MPAI-R) were administered to evaluate the anxiety levels of the students. This was followed by interview sessions with randomly selected participants. Through descriptive statistics and paired sample t-tests, this study suggests that the participants were afflicted with different levels of MPA in the first year (M = 127.379) compared to the second year (M = 138.621). There was a significant difference between the MPA level in the recorded assessment and the live assessment. The qualitative interview data were analysed through thematic analysis. The following themes emerged to reflect the factors that influence MPA. Mental/psychological stress was the emergent theme for internal factors, whereas environment, sound quality, and physical challenges were emergent themes for external factors. In conclusion, MPA levels of the students were high regardless of the assessment format and the factors that resulted in MPA varied according to the format.